2020
DOI: 10.3389/fchem.2020.00317
|View full text |Cite
|
Sign up to set email alerts
|

Methane Decomposition Over ZrO2-Supported Fe and Fe–Ni Catalysts—Effects of Doping La2O3 and WO3

Abstract: A leading method for hydrogen production that is free of carbon oxides is catalytic methane decomposition. In this research, Fe and Fe-Ni supported catalysts prepared by the wet impregnation method were used in methane decomposition. The effects of doping the parent support (ZrO 2) with La 2 O 3 and WO 3 were studied. It was discovered that the support doped with La 2 O 3 gave the best performance in terms of CH 4 conversion, H 2 yield, and stability at the test condition, 800 • C and 4,000-ml h −1 g −1 cat. s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…After passing this initial stage, hydrogen production and methane conversion gradually become stable with time on stream. In the case of the Fe promoter, improved stability at a given reaction time also was achieved in case of Ni‐Fe/ZrO 2 23,94 and Ni‐Fe/Al 2 O 3. 21 The addition of the second element as a promoter for Ni affords an alloy catalyst, which enhances the catalytic activity and stability, and the metal alloy increases the carbon diffusion rate and subsequently prevents deactivation 95 .…”
Section: Ni‐based Catalystmentioning
confidence: 88%
See 3 more Smart Citations
“…After passing this initial stage, hydrogen production and methane conversion gradually become stable with time on stream. In the case of the Fe promoter, improved stability at a given reaction time also was achieved in case of Ni‐Fe/ZrO 2 23,94 and Ni‐Fe/Al 2 O 3. 21 The addition of the second element as a promoter for Ni affords an alloy catalyst, which enhances the catalytic activity and stability, and the metal alloy increases the carbon diffusion rate and subsequently prevents deactivation 95 .…”
Section: Ni‐based Catalystmentioning
confidence: 88%
“…As oxide supports, metal oxides such as Al 2 O 3, 21,80,97,107 TiO 2, 108,109 SiO 2, 79,110‐114 MgO, 101,115 CeO 2, 100,116 ZrO 2, 23,94 and zeolite 22,104 are frequently used for a Ni‐based catalyst. In practice, active metal particles must be dispersed onto the oxide support surface.…”
Section: Ni‐based Catalystmentioning
confidence: 99%
See 2 more Smart Citations
“… 23 Fakeeha et al ; studied the effect of doping La 2 O 3 and WO 3 on the decomposition of methane by the Fe–Ni catalyst over the ZrO 2 support. 24 Their study revealed that the La 2 O 3 doped ZrO 2 support resulted in the maximum decomposition of methane to hydrogen with relatively high stability. Zhang et al ; investigated the stabilization of the metastable structure of ZrO 2 by reflux treatment and the improvement of Ni/ZrO 2 catalyst for CRM.…”
Section: Introductionmentioning
confidence: 99%